Cytotoxic KLRG1 expressing lymphocytes invade portal tracts in primary biliary cholangitis. (September 2019) - Li, Yikang; Li, Bo; You, Zhengrui; Zhang, Jun; Wei, Yiran; Li, You; Chen, Yong; Huang, Bingyuan; Wang, Qixia; Miao, Qi; Peng, Yanshen; Fang, Jingyuan; et al.
Abstract: Primary biliary cholangitis (PBC) is a chronic autoimmune liver disease with an immunopathogenesis that includes highly differentiated cytotoxic T cell infiltration in portal areas. We have taken advantage of a large and well-defined cohort of patients with PBC, AIH, chronic hepatitis virus, and healthy controls to study for the presence of highly differentiated T cells which express the killer cell lectin-like receptor G1 (KLRG1). Such studies were performed using both liver and peripheral blood mononuclear cells. In particular, gene expression data (GSE79850) from 16 PBC patients stratified according to future risk of liver transplantation were analyzed for markers of highly differentiated cytotoxic T cells. Liver biopsy samples from 44 PBC patients were studied by immunohistochemistry and a separate cohort of PBC blood samples were studied by flow cytometry. Gene expression data demonstrated correlation of increased KLRG1 and cytotoxic lymphocyte molecules, such as granzyme B ( GZMB ) and perforin ( PRF1 ), to disease severity as measured by future risk of liver transplantation. Immunohistochemistry demonstrated abundant infiltration of KLRG1+ cells into liver portal areas (mean of 45% of infiltrating cells, range 25–75%) positively correlated with hepatic inflammatory ( r  = 0.47, p = 0.001) and hepatic fibrosis ( r  = 0.34, p = 0.021) scores. KLRG1+ lymphocyte liver portal area infiltration was positively correlated with serum alkaline phosphatase ( r  = 0.45, p = 0.005) and GGT ( r  = 0.40, p = 0.014), and AST ( r  = 0.35, p = 0.033) levels. Mononuclear blood flow cytometry studies showed KLRG1+ lymphocytes had greater levels of cytotoxic molecules (granzyme B and perforin), inflammatory cytokines (IFN-γ and TNF-α) and inflammatory chemokine receptors (CCR5 and CX3CR1) than KLRG1-counterparts. However, clearly the most significant data was that found in liver with the intense portal infiltrates that are unique to PBC. Conclusion : Highly cytotoxic KLRG1+ lymphocytes have invaded PBC liver portal areas. Liver KLRG1 gene expression and the abundance of KLRG1+ lymphocytes are positively correlated with disease biomarkers used as clinical trial outcome measures (liver transplantation and serum alkaline phosphatase), suggesting the targeting of KLRG1+ lymphocytes as a rational approach for PBC therapeutic drug development. Highlights: Expression of liver KLRG1 is correlated to future risk of liver transplantation in PBC. Hepatic infiltrated KLRG1+ cells are correlated with disease severity in PBC. Circulating KLRG1+ lymphocytes are highly inflammatory cells. E-cadherin partially disappears in intrahepatic small bile ducts of PBC patients.